Les défis du « nouveau Népal » après les élections de l’Assemblée constituante - Tristan Bruslé (EchoGéo)
The elections of the Nepalese Constituent Assembly bring to a close thirteen years of civil strife. Now with the end of the Maoist rebellion, their surprise victory signals their entry onto the legitimate political arena in a most unfavourable socio-economic climate. The challenges facing the future government are commensurate with the expectations of the population, a third of which lives below the poverty level. Underdevelopment marks the daily lives of all the Nepalese; their social and spatial inequalities are greater than ever.